Assessment of regional ventilation by continuous inhalation of radioactive krypton-81m. Issue 5985 (20th September 1975) - Fazio, F; Jones, T
Abstract : A simple technique is described for producing high-quality functional images of regional ventilation during physiological tidal breathing of the inert gas 81mKr. These images are quickly obtained on a gamma-camera without the need of computerized systems for data acquisition and display and are directly comparable with those of perfusion obtained with 99mTc-labelled macroaggregates. The short time required for the procedure, its simplicity, and the extremely low absorbed-radiation dose enable serial images of ventilation to be obtained in multiple views.